2019
DOI: 10.1155/2019/3492767
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Capacity and Behavioral Relevance of a Polyphenolic Extract of Chrysanthellum americanum in a Rat Model of Irritable Bowel Syndrome

Abstract: Chrysanthellum americanum L. (Vatke) is a medicinal plant from the Compositae family used in west-African traditional medicine, known for its flavonoid and saponin richness and for its strong antioxidant potential. In the present study, we assessed the effects of Chrysanthellum americanum polyphenolic extract in the psychological stress-induced rat model of irritable bowel syndrome (IBS), a chronic functional digestive tract disorder marked by immune and inflammatory-related disturbances of central nervous and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 100 publications
2
19
0
Order By: Relevance
“…The screening of the different extracts revealed the presence of chemical interest groups in the selective extracts, namely terpenes, flavonoids, saponins and and phenolic acid. These results are consistent with the previous report on the phytochemistry of these different traditional drugs [9,13,23] . Preclinical studies have shown that certain compounds such as flavonoids, phenolic acids, saponins and terpenes, which have anxiolytic effects in a wide range of animal models, are involved in the treatment of mental disorders [22] .…”
Section: Phytochemical Screeningsupporting
confidence: 94%
See 1 more Smart Citation
“…The screening of the different extracts revealed the presence of chemical interest groups in the selective extracts, namely terpenes, flavonoids, saponins and and phenolic acid. These results are consistent with the previous report on the phytochemistry of these different traditional drugs [9,13,23] . Preclinical studies have shown that certain compounds such as flavonoids, phenolic acids, saponins and terpenes, which have anxiolytic effects in a wide range of animal models, are involved in the treatment of mental disorders [22] .…”
Section: Phytochemical Screeningsupporting
confidence: 94%
“…Plants, with their wide variety of chemical constituents, offer a promising source of medicines for many diseases, including mental disorders. This present study concerns Cymbopogon citratus, Lippia chevalieri, Combretum micratum, Chrysantellum americanum and Tetrapleura tetraptera involved in the treatment of mental illness [9,13] . These five plants have been used as herbal teas for years in some West African countries, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with irritable bowel disease (IBD) who is more like an organic disease, IBS lies more in the spectrum of functionality, gastrointestinal deficiency who has been associated with neuropsychiatric disturbances [38][39][40], due to prolonged exposure to stressful stimuli [34,35].…”
Section: Resultsmentioning
confidence: 99%
“…Still, the common ground between some of the mentioned psychiatric illnesses (which are subtypes of affective syndromes) and, according to ROME IV criteria, IBS is the lower or greater extent of stress axis impairment [47]. Previous studies have shown that oxidative stress changes also occurred in stress-based animal models [46,48,49]. This could be a specific piece of evidence that suggests that a central nervous modulation pathway is implicated in IBS pathophysiology, with oxidative stress being a possible signaling pathway but also an unwanted effect.…”
Section: Irritable Bowel Syndrome Pathophysiology and Promoting Factorsmentioning
confidence: 99%